1990
DOI: 10.1007/bf01325231
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic wasps orient to green leaf volatiles

Abstract: SummaryUndamaged plants emit low levels of green leaf volatiles (GLVs), while caterpillar-damaged and artificially damaged plants emit relatively higher levels of cerrain GLVs. Female braconid parasitoids, Microplitis croceipes, oriented to both damaged plants and to individual GLVs in no-choice tests in a wind tunnel, but seldom oriented to undamaged plants. Female ichneumonid parasitoids, Netelia heroica, also oriented to individual GLVs in a wind tunnel. Males of both wasp species failed to orient to the GL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(92 citation statements)
references
References 56 publications
3
88
0
Order By: Relevance
“…However, in our pear trees this green-leaf compound is clearly more abundantly released by infested plants and, therefore, using the same line of reasoning (Dicke et al, 1990a), we could have expected the bugs to respond to it, but they appeared not to. Also in cotton, (Z)-3-hexen-l-yl acetate was found to be associated with herbivory (McCall et al, 1994) and here parasitoids actually do respond to this and other green-leaf compounds (Whitman and Eller, 1990). Thus, it is not clear why anthocorids do not respond to the green-leaf compound, but do respond to the other two damage-related volatiles.…”
Section: Discussionmentioning
confidence: 79%
“…However, in our pear trees this green-leaf compound is clearly more abundantly released by infested plants and, therefore, using the same line of reasoning (Dicke et al, 1990a), we could have expected the bugs to respond to it, but they appeared not to. Also in cotton, (Z)-3-hexen-l-yl acetate was found to be associated with herbivory (McCall et al, 1994) and here parasitoids actually do respond to this and other green-leaf compounds (Whitman and Eller, 1990). Thus, it is not clear why anthocorids do not respond to the green-leaf compound, but do respond to the other two damage-related volatiles.…”
Section: Discussionmentioning
confidence: 79%
“…Odor released after recent damage is important also in attracting naïve C. marginiventris to cotton plants (Cortesero et al, 1997). Several parasitoids orient to individual green leaf volatile compounds in an olfactometer or flight tunnel tests (Whitman and Eller, 1990;Wickremasinghe and Van Emden, 1992;Reddy et al, 2002) or show strong electroantennogram responses to these compounds (Baehrecke et al, 1989;Li et al, 1992). However, there are exceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have suggested that some plants have evolved an indirect rritrophic mechanism of resistance in which they release compounds (synomones) after being fed upon that are attractive to predators or parasites of their herbivores (Turlings et al, 1990;Whitman and Eller, 1990). The plant could gain benefits if their herbivores are not attracted by these same host volatiles.…”
Section: Secondary Plant Compounds and Bark Beetle-tree Coevolutionmentioning
confidence: 99%